IMPLEMENTASI KEBIJAKAN SISTEM TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN PADA DAERAH KABUPATEN SUMBAWA - ZAIDURRAHMAN ZAIDURRAHMAN; SUPARMAN SUPARMAN; AHMAD YAMIN (Universitas Mahasaraswati K. Mataram, 2024)
This research discusses the implementation of non-cash transaction system policies in financial management in the Sumbawa district area. The aim of the research is to determine and analyze policies, supporting factors and inhibiting factors in the implementation of non-cash transaction system policies in financial management in the Sumbawa Regency area. This research uses a qualitative method with an interpretive descriptive approach. There were 5 informants for this research. Then, the data collection instrument was by means of interviews. The analysis technique used is data reduction and presentation. The results of the analysis consist of; 1. The process of implementing non-cash transactions in Sumbawa Regency is carried out by paying attention to four methods, namely staff-based, information, authority and facilities. 2. Supporting factors in the process of implementing non-cash transactions consist of internal control of regional finances, budget savings in non-cash transactions, and this non-cash transaction process can also prevent the circulation of counterfeit money. 3. Inhibiting factors in the process of implementing non-cash transactions consist of software, hardware and networks, the lack of competent employees, lack of staff understanding, leadership commitment, the presence of colleagues and employees who do not have the same account, and the use of cash payments in society. So it can be concluded that the implementation of the non-cash transaction system policy in financial management in the Sumbawa Regency area has been running in accordance with applicable guidelines